Reading Literacy Development Model as an Effort to Improve the Quality of Student Learning - Nurul Asma Khoiriyah; W Waston; Bambang Sumardjoko; Yassir Hafidh Fitriyan; Hana Ayu Safitri (Universitas Muhammadiyah Surakarta, 2025)
The phenomenon of low literacy quality in Indonesia is a very urgent problem to be overcome, considering that literacy is a basic skill that is very important for every individual, especially students. Literacy not only includes the ability to read and write, but also includes the skills of critical thinking, analyzing, and understanding information. With low literacy skills among students, this hinders their ability to access the more complex knowledge needed in later education. This study aims to identify and analyze the factors that affect the low quality of literacy in Indonesia and explore the development of innovative literacy teaching models that can be implemented in primary schools. In addition, this study also aims to provide recommendations for the development of education policies related to literacy. This research uses a qualitative approach with a library research method. Data was collected from relevant scientific literature, including journal articles, reference books, and conference articles. The main focus of this study is the text-based and technology-based literacy teaching model, as well as its relationship with students' critical thinking skills. The analysis technique used is thematic analysis to identify patterns and trends related to the research topic. Based on the research that was found, the low quality of literacy in Indonesia is caused by several factors, including lack of access to quality teaching materials, limited resources, and lack of teachers' skills in using technology in teaching literacy. The use of digital technologies such as e-books and gamification-based learning platforms can increase students' reading interest and improve their literacy skills. Literacy teaching models that integrate project-based and text-based approaches have proven effective in improving students' understanding and skills in literacy. This study concludes that to improve the quality of literacy in Indonesia, there needs to be reforms in teacher training, with a focus on integrating technology in literacy teaching. Teaching models that combine technology and text-based methods can be an effective solution to address literacy challenges in Indonesia. This research contributes to the development of literacy-based education policies that are more relevant and applicable at the elementary school level.